Impact of Rearing Rajasri Birds on the Livelihood and Nutritional Security of BPL Families in Warangal, Hanmakonda and Mulugu Districts of Telangana State - Saikiran, J.; Rajanna, N.; Shashank, J.; Ganesh, G.; Raju, A.; Sowmya, Ch.; Arunjyoti, R. (International Journal of Bio-resource and Stress Management, 2025)
The present experiment was conducted during January, 2022 to December, 2023 in Mulugu, Warangal and Hanmakonda districts of Telangana state, India to study on the generation of self-employment, provide supplementary income, and ensure access to protein food at a low cost. Backyard Poultry (BYP) was introduced by Krishi Vigyan Kendra Mamnoor as a livelihood initiative to improve the socio-economic conditions of Scheduled Caste and Scheduled Tribe communities. In 2022 and 2023, over 9,870 vaccinated Rajasri birds were distributed to 987 beneficiaries across the 11 villages under the Scheduled Caste and Tribal Sub Plan programs. Each farmer received a unit of 10 Rajasri birds, valued at ` 1000, along with supplementary medicines and vaccines. The study found that Rajasri birds attained sexual maturity at 165 days, with an average body weight of 1200–1300 g under scavenging conditions. They produced an average of 1200–1300 eggs per unit over 52 weeks, with each egg weighing 45–50 g. This generated a net average annual income of `Rs. 7,930.27 from the sale of eggs and male birds through Backyard Poultry. There was also a notable increase in egg and meat consumption among SC/ST families. On average, each unit of Backyard Poultry produced 933 eggs annually. The per capita egg consumption in the villages increased effectively along with supplementary income, chicken meat, and eggs as well as poultry manure for enhancing soil fertility.